Cartographic Materials as a Means of Multimedia Communication - Sowa-Babik, Halina (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
In the early 15th century Gutenberg revolutionized the world by making possible the propagation of knowledge by printing. Today, with the appearance of individual multimedia computers, traditional maps tend to be replaced by maps on optical disks (CD-ROM) and Internet distributed resources that enable one to stock not only text, but also sound, static and animated images as well. What does this mean for cartographic materials(CMs) collection in libraries? Cartographic materials existed long before anyone dared to dream about computers. Various Information Technologies (ITs) are as old as the human desire to gather information and pass it from one person to another. Information and communication technology (ICT), understood as a technique of storing and transferring information, is an integral element in the process of communication. Technological evolution changes the way we communicate through cartographic materials in many areas of activity in science. In our article, we concentrate on certain selected aspects of this communication. We look at how IT has affected the process of CMs communication and how CMs can be accessed by the users potentially interested in them. We claim that the current transformations in ICT redefine the roles of the CMs usually regarded as an information (re)source, an information provider, and the reader/user, a (passive) recipient of the information provided by the CMs. The problem we are going to deal with is the following: can cartographic materials be included in the class of multimedia documents? If so, when and in what sense? The starting point is to concentrate on the dependence of access to information contained in cartographic materials on information carriers. At the same time, we would like to mention the difference between access to information and the skills needed for using it.